Предмет: Алгебра,
автор: aleksandrakudrashova
найдите значение выражения.
(с² + 3) (с - 9) -с² (с - 6) при с = -5
Ответы
Автор ответа:
2
Ответ:
(25+3)(-5-9)-25(-5-6)=27*(-14)-25*(-11)= -378-275= -653
Объяснение:
-653
aleksandrakudrashova:
это не верно (
Автор ответа:
2
Ответ: (25+3)*(-5-9)-25*(-11)=28*(-14)+25*11=275-392=-117.
Объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: sutyagina2003
Предмет: Русский язык,
автор: annailiadi128
Предмет: Алгебра,
автор: ekurugliyeva
Предмет: Алгебра,
автор: romanovromanovmaiu